Microstructures and mechanical properties of YG18 cemented carbide/40Cr steel joints vacuum brazed using Ag–Cu–Ti filler metal. (October 2022) - Zheng, Zhaoyang; Wang, Shaoheng; Xu, Minyun; Du, An; Ma, Ruina; Fan, Yongzhe; Zhao, Xue; Cao, Xiaoming
Abstract: YG18 cemented carbide and 40Cr steel were brazed using Ag–Cu–Ti filler metal under vacuum, and the microstructural evolution of the YG18/Ag–Cu–Ti filler metal/40Cr steel brazed-joint interface was investigated to determine how brazing temperature affected the brazed-joint microstructure, bonding strength, and fracture behavior. At the YG18 cemented carbide/filler metal interface, Ti atoms in the filler metal and C atoms in the YG18 cemented carbide formed a continuous TiC layer, reducing the difference in thermal expansion coefficients between the YG18 cemented carbide and filler metal. At the 40Cr steel/filler metal interface, Ti atoms in the filler metal and C atoms in the 40Cr steel formed a continuous TiC layer, preventing the diffusion of Fe atoms to the cemented carbide side and formation of a hard, brittle phase. YG18 cemented carbide/TiC/Cu2 Ti/Ag–Cu eutectic + TiCu granules/TiC/40Cr steel-brazed joints were obtained. With increasing brazing temperature from 860 to 920 °C, the bonding strength of the YG18 cemented carbide/40Cr steel joint initially increased and then decreased. The joint brazed at 900 °C for 10 min failed in the middle of the brazing seam, and its average bonding strength was 235 MPa. Highlights: The connection of YG18 cemented carbide and 40Cr steel with Ag–Cu–Ti filler metal was prepared by vacuum brazing. At the interface between the YG18 carbide and filler metal, a continuous layer of TiC was obtained, resulting in the reduction of the difference in the thermal expansion coefficient (CTE) between the YG18 cemented carbide and filler metal. At the interface between the 40Cr steel and filler metal, the formation of a continuous layer of TiC prevented Fe atoms from spreading to the cemented carbide side to avoid the formation of a hard brittle phase. The joint brazed at 900 °C for 10 min failed in the middle of the brazing seam, and its average bonding strength was 235 MPa.